Impact of irrigation works systems on livelihoods of fishing community in Ca Mau Peninsula, Viet Nam - Van, M.V.; Hien, H. V.; Phuong, D. T.; Quyen, N. T. K.; Nga, D. T. V.; Tuan, L. A. (2016)
Ca Mau Peninsula (CMP) locates in Mekong Delta, Vietnam is a conflict area in the use of freshwater and brackish water due to existing of both types of ecosystems. The irrigation works systems (IWS) in CMP were planned and constructed to serve local communities’ economic development. The aims of this study are to investigate the impact of irrigation works on livelihoods of fishing community in Ca Mau Peninsula, Viet Nam. The study was conducted in six communes in five districts in the two provinces, Can Tho City (freshwater ecosystem) and Bac Lieu province (brackish water ecosystem). Six Rapid Rural Appraisal (PRA) meetings were held, four meetings located in the affected area of IWS (120 households) and two adjacent areas, which were not affected by IWS (120 households). Data on fish species compositions were collected three times a year. This paper argues that the highly construction inside IWS area caused lower fish species composition and lower fish production inside IWS area compared to outside IWS area in both freshwater and brackish water ecosystems. Limited households inside IWS area (9.3%) and outside IWS area (17.8%) involved in local associations fishing community in both ecosystems and they mostly had a very low annual accumulate income. Net, trap, mud chain, trawl and fishing rods were five main types of fishing gears of the professional fishing households. Survey result also shows that the majority of fishermen understood rules relating to activities of aquatic resources protection and management of the provinces though 25-30% of households still did not know anything about these regulations. Overall results revealed an impact of IWS on livelihoods of fishing community such as human resources, natural resources and physical capital. Therefore, there are urgent needs on training on the fishery regulations for fishermen in the regions focused on appropriate fishing gear, mesh size net, fishing ground and fishing seasons. In particular, investment in education and career training to improve opportunities to access employment for the community become necessary.